Tradisi Martahi (Musyawarah) Masyarakat Desa Mandasip Suku Mandailing - Nasution, Saripa Haribulan; Dora, Nur Iza (JURNAL EDUKASI NONFORMAL, 2023)
This research aims to describe the value of martahi in mandasip village communities in the context of parties such as custom parties,marriage and child marriage The purpose of this study is to find out the picture and value of the implementation of martahi in mandasip communities This research uses a qualitative descriptive approach to data collection conducted with in-depth interviews with informants, documentation and participatory observations. Then carry out data analysis techniques by making an interview analysis and writing The results of this study can be known that the local wisdom of Martahi in the village community mandasip has the value and meaning of unity, brotherhood, togetherness, help each other for rural communities. The village community mandasip sub-district sub-district is an ethnic Batak Mandailing, and Toba. Local values and meanings based on Martahi's wisdom in society are maintaining harmony and brotherhood between communities.